Doing Business in Central America and the Dominican Republic 2015 : Overview - World Bank Group (Washington, DC, 2015)
The strengthening of sustained and inclusive economic growth providing opportunities for all and reducing inequality is a key to achieving shared prosperity in Central America and the Dominican Republic. However, the countries in this region except for Panama and Costa Rica have not yet attained growth driven by high productivity. Foreign trade grew less in Central America than in other regions. Other studies reveal that the areas having the greatest impact on trade costs and volumes are information availability, process improvement through the use of online tools, and document simplification and streamlining. The strengthening of the business environment is a key action within these countries' competitiveness and productivity agenda. If laws and regulations are clear, accessible, and transparent, while at the same time they are enforceable before a court of justice if necessary, entrepreneurs will have more time to devote to productive activities and will feel more confident to run the risk of doing business with people they don't know, which may contribute to the expansion of their client and supplier network, thereby making their business grow. Doing business in Central America and the Dominican Republic 2015 for the first time includes a gender perspective based on the study of the laws and regulations that impose differential treatment for women.